A Rare Case of Small Intestinal Cancer With Uterine Metastasis After Surgery for Ovarian Metastasis, Diagnosed Using Immunostaining - Sachiko Nagao; Motoki Matsuura; Shoko Kurokawa; Masato Tamate; Taishi Akimoto; Tsuyoshi Saito (Case Reports in Oncological Medicine)
Uterine metastases from extragenital sites are rare. We present a case of a woman who had undergone surgery for small intestinal cancer and subsequently developed metastases in her left ovary and uterus. A nulliparous woman in her 50s underwent laparoscopic partial small bowel resection with lymph node dissection for small intestinal cancer. Five months later, computed tomography (CT) revealed a left ovarian tumor and ascites. She underwent bilateral adnexectomy and adjuvant chemotherapy, and the ovarian tumor was diagnosed as a small intestinal cancer metastasis. Two years after the small intestinal cancer surgery, a positron emission tomography (PET)-CT scan revealed a uterine accumulation. Cervical cytology was negative for intraepithelial lesion or malignancy. Endometrial histology showed an adenocarcinoma of the uterus. The patient underwent total abdominal hysterectomy followed by adjuvant chemotherapy. Histopathology and immunohistochemistry of the uterine tumor revealed that it was a metastasis of small intestinal cancer (Cytokeratin 7 [CK7] [−], Cytokeratin 20 [CK20] [+], Special AT-Rich Sequence-Binding Protein 2 [SATB2] [+], Paired Box Gene 2 [PAX2] [−], and estrogen receptor [ER] [−]). In patients with cancer, histopathology and immunohistochemistry are important for distinguishing between primary and metastatic tumors and for guiding the choice of treatment.